Exogenous sources of regional industrial change: Attraction and absorption of non-local knowledge for new path development - Trippl, Michaela; Grillitsch, Markus; Isaksen, Arne (Progress in human geography, 2018)
The role of exogenous sources of new path development has been underplayed in the literature on regional industrial change so far. The aim of this article is to explore in a conceptual way under which conditions and in what ways non-local knowledge can lead to new path development in different regional innovation systems (RISs). We distinguish between organizationally thick and diversified RISs, thick and specialized RISs and thin RISs and argue that these types vary substantially in their needs for exogenous sources as well as in their capacities to attract and absorb knowledge generated elsewhere.